ANALISIS IMPLEMENTASI 5C BANK BPR DALAM MENENTUKAN KELAYAKAN PEMBERIAN KREDIT PADA NASABAH ( Studi Kasus Pada PD BPR Bank Salatiga Dan PT BPR Kridaharta Salatiga) - Afandi, Pandi (AMONG MAKARTI, 2010)
Abstract BPR represent the institute intermediasi to owning fund and require the fund from society, One of [he product BPR is credit channelled to client. Problem of credit which often emerge is the existence of NPL (non performance loan) or credit height stuck. For that need the carefulness in channelling credit to client so that to be credit channelled improve the benefit to client. the Carefulness approach done/conducted with the analysis of elegibility of giving] credit to client through the analysis 5C ( character, capacity, capital, colleteral and condition of econom) so that the target of this research is to know how the BPR-BPR is implementation 5C to the client perception at PD BPR of Bank of Salatiga and client of PT BPR Kridaarta Salatiga, what differing or do not by using Statistic of nonparametrik Mann-Whitney U tes. Result of hypothesis test indicate that the aspect of character and condition of economy each showing asymp sig of equal to 0,552 and 0,028 bigger than = 0,05 so that do not its signifkan meaning there no difference of implementation of aspect of character and condition of economy as determinant of elegibility of giving credit of either by PD BPR of Bank of Salatiga and also PT BPR Kridaharta Salatiga. While from aspect capacity, capital and collateral obtained by asymp sig of each of 0,000 and 0,007 and also 0,000 smaller than = its 0,05 meaning there is implementation difference which signiikan in determination of giving credit to client of good to PD BPR of Bank of Salatiga and PT BPR Kridaharta Salatiga. Result of total test at 5C obtained by asymp.sig of equal to 0,001 smaller than = 0,05, its meaning there is implementation difference which signifikan of[is overall of aspect character, capacity, cpital, collateral and condition of economy in determining elegibility of pemebrian credit to client between PD BPR of Bank Salatiga by PT BPR Kridaarta Salatiga. Paying attention elegibility aspect in [gift/ giving] of credit and follow-up from this research result to be developed by variable and indicator empiriknya with the other analysis is suggestion given from this research solution result. Keyword : 5C, Character, Capacity, Capital, Colleteral And Condition of economy.